METHODS OF IMPROVEMENT OF PEDAGOGICAL THESIS - Vladimir D. Shadrikov; Nikolai Kh. Rozov; Alexey V. Borovskikh (Moscow Polytechnic University, 2016)
The article addresses tools that can tangibly improve the quality of theses on pedagogical sciences. First, we point out that no repressive measures taken by the Higher Attestation Commission (HAC) and dissertation councils can affect the quality of theses, because they regard thesis that have j ust been written. As the main problem the authors mark out social inertia. Overcoming of a formed tradition requires more than administrative measures but the formation of social and scientific mechanisms providing scientific rigor and relevance of a study. These are three mechanisms: a system of specialized scientific conferences (in the worst case - within HAC specialty, but differentiated thematically is more desirable), the system of specialized scientific seminars and the system of specialized scientific journals. All three systems work effectively in other sciences, both natural and human, and ensure the formation of investigator's adequate ideas about the obj ectives, goals, and problems of his research at the stage of its beginning, and not when it is already completed. Formation of the first two of these systems at least requires no additional resources except self-organization and volition of scientific community.